Crossroads—Commentary: What Is Problematic about a Discourse Called “Unproblematic”? - Scully, Maureen A. (Organization Science, 1998)
This paper on discourse makes for lively reading, because it offers such rich examples of the discourse it analyzes. At different points in the paper, the author refers to the idea that “discourse creates institutions” as well as the idea that “institutions create discourse.” The power of discourse is that it creates a circular thread whose beginning and end are hard to find. This paper is therefore especially helpful by analyzing a discourse at the time it is fabricated, to trace how the reinforcing loop is set in motion. Moreover, the author does not lose sight of how the circle might be broken. While many accounts of strong social forces overlook the possibility of resistance, this paper remembers to look for glimmers of resistance and remark on the significance of their absence.